2013
DOI: 10.1007/s00247-013-2726-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and relevance of pediatric spinal fractures in suspected child abuse

Abstract: Spinal fractures are not rare in children with positive skeletal surveys performed for suspected abuse and they may be the only indication of skeletal trauma. There is an association between spinal fractures and ICI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 27 publications
0
30
1
Order By: Relevance
“…This study was limited to children ,24 months old. A recent study of SS1 found a higher incidence of spine fractures in children .24 months old than in children ,24 months old 28 ; thus, our results may not be freely generalized as to age. Finally, SS2 were obtained in only 27.2% of our eligible subjects.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…This study was limited to children ,24 months old. A recent study of SS1 found a higher incidence of spine fractures in children .24 months old than in children ,24 months old 28 ; thus, our results may not be freely generalized as to age. Finally, SS2 were obtained in only 27.2% of our eligible subjects.…”
Section: Discussioncontrasting
confidence: 70%
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28] The small number of these fractures, and their frequent association with other evidence allowing the diagnosis of abuse, has triggered a suggestion that spine and pelvis views be omitted from SS1. 24,26 Others have opposed this viewpoint for spine fractures, 25,27,28 making the argument that there is high specificity for abuse when occult spine fractures are discovered, and that spine fractures, while uncommon, are not rare. The low initial prevalence of spine and pelvis fractures on both SS1 and SS2 supports decreasing repeated exposure by eliminating these views from SS2.…”
Section: Discussionmentioning
confidence: 99%
“…3,40,54 In infancy, excepting cases of abusive head injury, the rates of spinal injury associated with TBI have seemed to be quite low. 2,8,19,30 The current study reports spinal injury rates of 9.8% for NTDB admissions coded for TBI and 10.9% for admissions coded for GCS motor ≤ 4, but all spinal levels have been counted. Among admissions of patients whose clinical evaluations were obscured by intubation or sedation, the current study notes a prevalence of spinal injury of 16.7%.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported a significant correlation between spinal fractures and intracranial injury (Fig. 4) [23]. Ten of 14 (71%) children with spinal fractures had intracranial injury; eight children had a combination of unilateral or bilateral subdural hematomas and brain parenchymal injury or subarachnoid hemorrhage suggestive of abusive head trauma [23].…”
Section: The Classic Metaphyseal Lesionmentioning
confidence: 97%
“…Ten of 14 (71%) children with spinal fractures had intracranial injury; eight children had a combination of unilateral or bilateral subdural hematomas and brain parenchymal injury or subarachnoid hemorrhage suggestive of abusive head trauma [23]. One of these children had an unsuspected skull fracture on skeletal survey with MRI findings suggesting hemorrhage along the margins of the tentorium and mild restricted diffusion in the cerebellar hemispheres [23]. Another child presented with right hemiparesis had brain MR findings initially interpreted as consistent with an acute ischemic injury; Fig.…”
Section: The Classic Metaphyseal Lesionmentioning
confidence: 99%